PENGARUH GAYA KEPEMIMPINAN TERHADAP PRESTASI KERJA PEGAWAI PADA DINAS ARSIP DAN PERPUSTAKAAN DAERAH KABUPATEN BOGOR - teni agustina (Widya Cipta - Jurnal Sekretari dan Manajemen, 2018)
Abstract  –  Manage by the leadership style of a leader is the proper techinique undertaken to improve the quality of human resourcesin order to produce optimal performance in achieving a common goal. This study aims to determine the effect of leadership style to the achievement of employee’s work at Departement of Archives and Regional Library of District Bogor. The methodology is primary quantitative methodology. Document were obtained through surveys and questionnaire, and  samples taken using saturated sampling where all employee at Departement of Archives and Regional Library of District Bogor to be respondent, as many as 45 respondents. Research methodology consist of the Scale Likert, Correlation Product Moment consist of : correlation coefficient, coefficient determination, regression equation, test statistic with SPSS 21. Correlation coeficient receive is 0,733 it means there is a connection between leadership style and work achievement. The coeficient determination is 54% influenced by leadership style and 46% influenced by onother factor. And reggresion equation test Y = 22,038 + 0,524X, analyzable first : if X = 0 or without any leadership style then the work achievement is (22,038). Second : if the leadership style rises 1 point that will be increase work achievement (22,562).